A Shear-Sliding Rigid-Flexible Coupled Skin Variable-Sweep Wing Design and Heat-Fluid-Structure Multifield Coupling Analysis - Hong Xiao; Hongwei Guo; Mingqi Li; Yu Zhang; Rongqiang Liu; Jianguo Tao (International Journal of Aerospace Engineering)
The variable-sweep wing is very attractive for cross-speed domain aircraft. The shear-sliding rigid-flexible coupled skin variable-sweep wing and its associated mechanism are designed and optimized. The variable-sweep wing has smooth continuous deformation and rigid-flexible coupling features. The calculation model of the sliding skin patch segmentation strategy is established, and the aerodynamic characteristics of the two-dimensional airfoil before and after the deformation of the wing skin are analyzed. According to the deformation characteristics of sliding skin, the configuration of the associated mechanism is determined, and the kinematic characteristics of the reference points of each skin are calculated. The kinematic simulation verifies the force of the mechanism model at the joint of skin surfaces during the deformation process. Considering the aerodynamic heat at supersonic speed, the heat transfer, heat distribution, and structural thermal modes between the flow field and the skin are calculated based on the finite element method. The dynamic characteristics of the swept wing with different flight speeds and different morphologies are analyzed. The natural frequencies are found to be reduced by about 30% to 50% compared to cold models at supersonic speeds. Based on the results of the thermal fluid-solid coupling calculation, the skeleton structure of the swept wing is optimized, and the skeleton structure with 25% mass reduction and better performance is obtained.